Edge chemistry and tensile strain effects on the magnetic properties of 1D VSe2 structures. Issue 37 (27th August 2021) - Chen, H. L.; Zhang, L.; Deng, X. Q.; Sun, L.; Zhang, Z. H.; Fan, Z. Q.
Abstract : The first-principles calculations show that the simple edge chemistry can make VSe2 armchair ribbons generate various favorable magnetic phases, and the tensile strain can flexibly tune their magneto-electronic properties. Abstract : Recently, a successfully fabricated H–VSe2 monolayer, behaving as a ferromagnetic (FM) bipolar magnetic semiconductor, has attracted intense research interest. Here, to enrich its magnetic properties and expand its realistic application scope, we study quantum manipulations for its 1D structure, including edge chemistry and tensile strain modulation effects, and the underlying physical mechanisms. Interestingly, it is found that a simple edge chemistry effect can make armchair nanoribbons generate almost all favorable magnetic phases in the FM ground state, including half-metal, half-semiconductor, bipolar magnetic semiconductor, and magnetic metal phases, which are the basis for developing advanced multi-functional magnetic devices. The magneto-electronic properties of these chemically modified nanoribbons are also flexibly tunable by the tensile strain, for example, inducing diverse magnetic phase transitions, increasing the magnetic moment, and enhancing the Curie temperature beyond room temperature, which is closely related to the magnetic mechanism superposition of double exchange effects and superexchange interactions upon the tensile strain. Furthermore, the functionalized ribbon-based multi-functional magnetic device properties are tested, and the excellent single and dual spin filtering effects, spin-dependent rectification behaviors, and giant magnetoresistance effects are predicted. Overall, these findings open up a new avenue for designing multi-magnetic phase materials and multi-functional magnetic devices.